Saranjana in Historical Record: The City's Invisibility in Pulau Laut, South Kalimantan - Mansyur Mansyur (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2018)
Saranjana is a mystical city that is a myth for the people of Pulau Laut, South Kalimantan. Rumours about this mysterious city became increasingly excited because its existence, but not recorded on the map of Indonesia. Therefore it is very interesting to examine from a historical point of view. The purpose of this paper is to uncover the historical side of the occult city suggestion on Pulau Laut. This study using the method of history is a method to test and analyze the critical records and relics of the past. The historical method consists of four stages, namely heuristics (data collection), source criticism, interpretation (interpreting facts) and historiography. The results show exist of Saranjana in a place between fact and myth. In conclusion, there are two hypotheses that the Saranjana is ethnic state Dayak Samihim tribe. Then the second hypothesis, that Saranjana is (only) the dream country of Prince Purabaya in the 18th century AD.